Parasympathetic Reactivity and Oxidative Stress among Participants Suffering from the Polycystic Ovarian Syndrome - Shazia Sukhera, Jawaria Ilyas, Shama Iqbal, Maryam Mastoor, Qamar Zaman, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Burden of PCOs is increasing throughout the world with a prevalence of 8% - 13% of females getting affected around the globe. Many studies have also reported autonomic dysfunction among participants with PCOs with poor response to the parasympathetic nervous system and increased response to the sympathetic nervous system in contrast to that in normal counterparts. This study will aim to assess the parasympathetic reactivity of the cardiac system and oxidative stress among participants suffering from PCOs in a tertiary care hospital in Pakistan. Females with PCOs will be compared to normal counterparts of similar age and weight. Methodology: A cross-sectional study was conducted in the Department of Physiology of Jinnah Hospital, Lahore Pakistan from January 2021 to December 2021. Participants were recruited by purposive sampling following meeting inclusion and exclusion criteria. PCOs participants were matched with non-affected females with similar weight and age. The participants were assessed for oxidative stress by undergoing examination of serum catalase and MDA levels. Autonomic reactivity was assessed by recording ECG on taking deep breaths, on standing and following Valsalva maneuver. Both groups were compared for outcomes and measurement. Results: The outcomes of this study showed that the group with PCOs females showed a significantly higher rate of heartbeat per minute, resting systolic and diastolic blood pressure in comparison to their normal counterparts. The serology reports showed PCOs affected group to have lower levels of catalase and increased levels of MDA in opposition to non-affected females. Furthermore, it was seen with serology and ECG measurement that E: I ratio, E-I difference, 30:15 ratio, and Valsalva ratio were all found to be positively associated with levels of plasma catalase, whereas all measurements were negatively associated with serum MDA levels in a group consisting of PCOs affected females. Conclusion: This study concludes that a variation is seen in the parasympathetic stimulation among participants suffering from PCOs and this alteration of autonomic reactivity correlates to reduced response to parasympathetic inputs leading to a deficiency. The results of the study did not signify ay neuropathy which could be suggested by measurement of assessment of cardiac autonomic function. However, it cannot be overlooked that these measurements were different from that of normal counterparts. Lower catalase levels and increased levels of MDA among the PCOs group signify oxidative stress.